USING AGGREGATING DEVICES TO SAMPLE FISH RECRUITS AROUND DEEP SHIPWRECKS: EXPERIMENTS AND SUGGESTIONS - Mendes de Barros Correia, José Renato; Gomes da Silva, Erandy; França Schettini, Carlos Augusto; Pacheco dos Santos, José Carlos; Hilário Pedrosa Campello, Tiago; de Araújo, Maria Elisabeth (Arquivos de Ciências do Mar, 2020)
Fish aggregating devices (FAD) are an ancient fishery technique that benefits from the gregarious behavior of many species. They represent alternatives to usual census approach to study fish recruits. Based on this, we test two FAD models built for fish recruitment research, Standard monitoring unit for the recruitment of reef fishes (SMURF) and Artificial Reef Mooring (ARM) moored for the first time close to deep shipwrecks in Brazil Northeastern coast. We compared fish recruits’ abundance sampled by both models at two depths, bottom and mid-water (6 meters from the bottom). SMURFs sampled seven times more fish recruits than ARM with no difference between depth. We discovered that SMURFs mooring tilted 24º in mean with local marine currents. A long-term study with SMURFs tested immersion time influence in recruit’s sampling, and explored recruit’s abundance and standard length at two depth from the bottom. Increasing immersion time from 14-28 days did not influence recruit’s abundance. Bottom and Mid-water SMURFs sampled equal recruit’s number and fish sizes were significantly larger at the bottom. FADs, specially SMURFs, showed good tool to sample fish recruits in deeper shipwrecks,however standardization of FAD deployment is indicated to maximize work time and security in unstable sea conditions.